Review and Comparison of Content Growth in Word Definition of Persian Speaking Children of 7-12 Years of Age - Shima Matloubi; Talieh Zarifian; Tahereh Sima Shirazi; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective Language has three components: content, form and pragmatic. The content includes the semantic components. Semantic knowledge of word relationships requires awareness of the relationships between different words in the same field and other fields. One of the main components of the semantic is the mental lexicon that many of the semantic communications, including the organization and semantic representations of words, take shape in this network. The important issue is how to organize words in mind, linking the words together and their position in the semantic network. One task that helps to organize the meanings of the words in the mental lexicon is the word definition task. The ability to define words is reliant o  several aspects of linguistic and metalinguistic  development, literacy, and academic achievement. The aim of this investigation was to study the definitional style of nouns in typically developing school-aged children.  Materials & Methods In this cross-sectional and descriptive-analytical study, 150 typically developing school-aged children, selected using multistage sampling method, studying in the second to sixth grades in 1, 7 and 17 municipal districts of Tehran were included. The definition skill was assessed with word definition task. The students were asked to define the words, and their answers were scored based on content. The reliability was assessed by two independent values, and the validity was determined by the content. The results were analyzed by the SPSS V. 22 software using the methods of independent- samples T test, univariate analysis of variance and Tukey’s test. Results The findings showed that by increasing the age, the noun definitions were developed from functional and concrete responses into combination two and using of superordinate terms were increased. The mean score of the content in word definition was significantly increased by age (P<0.001). Also the performance of girl students was better as they earned higher scores than the boys (P=0.03).  Conclusion  On increasing the age, the content quality of word definitions improved significantly. The concepts were found to be organized into hierarchies of connections. Also, definitions were developed from functional and concrete responses into combination two and formal responses. And finally, the word definition task can be used by speech and language therapists in clinical and educational environments.